Is accounting education sufficiently sustainable?. Issue 1 (11th February 2014) - Botes, Vida; Low, Mary; Chapman, James
Abstract : Purpose: – This study aims to examine to what extent and how effective sustainability education has been at the tertiary accounting education level. The New Zealand (NZ) Parliamentary Commissioner for the Environment identified that sustainability education, as part of university education, is important, though NZ universities currently perform poorly in this area. This study looks at the important issue of sustainability education in the context of the emerging field of ecological economics and new understanding in business role and function of society where accounting education represents the precondition in meeting the challenges successfully. Design/methodology/approach: – A mixed method approach was used for this investigation combining quantitative and qualitative research methods to provide more depth to the analysis. Both interviews and online surveys were conducted to determine the perceptions held by both academics and graduates, of the extent and adequacy of sustainability education with NZ university degrees. An extensive review of the literature and the overview of the web sites of the different universities formed the qualitative part of the mixed method research approach to the investigation to determine the state of sustainability education in accounting courses at NZ universities. Findings: – There were mixed views on the current state of sustainability education within NZ university accounting courses. Although there was a general consensus with both groups of participants that a start has been made, the integration is not wide enough and the sustainability education is not in sufficient depth. There were mixed feelings regarding the role that accountants should play in sustainability reporting; however, there was a general consensus around the fact that accountants do have a role to play. Both groups of participants indicated that it is important for sustainability education to be included in accounting courses at NZ universities. Based on the research findings, it appears that universities have to maintain or provide an optional higher undergraduate or post-graduate level paper in sustainability accounting. Evidence from lecturers' personal experience suggest that these courses better develop a student's knowledge of sustainability as they have time to take an interdisciplinary approach to teaching and take a look at "big issues" like how accounting can either support or hinder sustainability directions for businesses and society. Originality/value: – The role that accounting educators play in integrating sustainability education at universities has been a contentious issue with a seemingly large gap between what research has defined as best education practice and what is currently being taught around the world. Although sustainability has formed the subject of extensive research over a number of years, there has been no work performed on the current state of sustainability education in accounting courses at NZ universities. Given the future challenges that NZ managers (and accountants) will face, it is important that universities which form a vital part of NZ society, equip managers (and accountants) to meet these demands. This study on perceptions of different stakeholders in relation to education for sustainable development, therefore, provides really important arguments for why there has to be further developments in this crucial area. The findings indicate that sustainability education by accounting educators is on a very much ad hoc basis. Further research needs to be conducted to drive better educational directions in sustainable development in universities.